PENGARUH MEDIA CETAK TERHADAP KEMAMPUAN MENULIS KARANGAN ARGUMENTASI - Candra R Gultom (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2014)
This study aims to describe the influence of newspaper print media on the ability to write  essays  argumentation  class  X  SMA  Santa  Lucia  learning  year  2012/2013.  The population  of this  research  is  all class  X  SMA Santa Lucia Sei  Rotan consisting of fourclasses with a population of 130 students. Of the number of students was assigned a samplethat  is 64 people. The  method  used is an  experimental  method that compares two groups,given learning to write essays arguing with print media newspapers or experimental class (X) and  the  group  learning  with  print  media  textbook  or  classroom  control  given  different treatment.Experimental class  data captured argument essay  writing essay test using compiledfor the goals to be achieved. Prior to the analysis of data, analysis persayratan test is a test of normality and homogeneity  tests. Distribution data  obtained: the  experimental  class has  an average of 79.34 with a standard deviation of 6.72 and a control class has an average of 67.31and a standard deviation of 8.07. The results of the normality test calculations obtained: an experimental class to obtain price Lo (Lhitung) = 0.13 and Lt (Ltabel) = 0.15. Turns Lhitung<Ltabel or 0.13 <0.15 which argument essay writing using print media newspapers normal distribution; and gain control class price Lo (Lhitung) = 0.07 and Lt (Ltabel) = 0.15. TurnsLhitung <Ltabel or  0.07 <0.15. It  is proved that  the learning outcome  data write  essaysarguing with print media textbook normal distribution. The results of the combined variance homogeneity test calculations studied two groups obtained X2hitung = 1.42 and X2tabel =1.84. Price X2hitung <X2tabel namely 1.42 <1.84. Hypothesis  testing  is  done mendenganusing 't' test. From the calculation hypothesis test obtained t = 6.39 ttabel further consultationwith the significance level of 5% with df = (N1 + N2) - 2 = 60. In the table t with df = 60obtained ttable significance level of 5% = 2.00. Testing criteria states that Ha accepted if t count> t  table  (6.39> 2.00), then  the  alternative  hypothesis  is  accepted  that  states  the newspaper print media better than the print media by increasing the letter textbook writing essays argument proceeds learn some vital lessons.Keywords : Media Print, Write essays argumentation